Relationship between fetal growth and the development of asthma and atopy in childhood. Issue 10 (1st October 1999) - Leadbitter, Philip; Pearce, Neil; Cheng, Soo; Sears, Malcolm R; Holdaway, M David; Flannery, Erin M; Herbison, G Peter; Beasley, Richard
Abstract : BACKGROUND: A study was undertaken to investigate the relationship between birth anthropometric measures and the subsequent development of asthma, airway hyperresponsiveness, and atopy in later childhood. METHODS: A longitudinal study was performed on 734 subjects (71%) from a cohort of children born in Dunedin, New Zealand in 1972–73. The birth anthropometric measures were available from hospital records and the main outcome measures of reported asthma, skin prick tests, and methacholine hyperresponsiveness were measured at the age of 13 years, while the serum total IgE was measured at 11 years. RESULTS: After adjustment for other factors, infants with a larger head circumference at birth tended to have higher serum total IgE at 11 years of age (p = 0.02) but IgE was not associated significantly with birth length or birth weight. The adjusted odds ratio for raised serum IgE (>150 IU/ml) in infants with a head circumference of 37 cm or more was 3.4 (95% CI 1.4 to 7.9). In contrast, recent asthma symptoms were positively associated with birth length (p = 0.04) but not with head circumference. The adjusted odds ratio for asthma in the previous two years in infants with a birth length of 56 cm or more was 6.4 (95% CI 2.0 to 19.8). Infants with a birth weight of less than 3.0 kg had an odds ratio for reported asthma of 0.2 (95% CI 0.0–0.6). There were no significant associations of any of the birth parameters with skin prick positivity, reported hay fever, or eczema. CONCLUSIONS: These results suggest that increased fetal growth is related to an increased risk of asthma and atopy in childhood. The precision of the findings is limited by the small numbers in the extreme categories of each birth parameter, but the results are consistent with intrauterine programming of the developing respiratory and immune systems.